Diabetes, Prediabetes, and Brain Volumes and Subclinical Cerebrovascular Disease on MRI: The Atherosclerosis Risk in Communities Neurocognitive Study (ARIC-NCS) - Schneider, Andrea L.C. (Diabetes Care, 2017)
OBJECTIVE: To examine the associations of prediabetes, diabetes, and diabetes severity (as assessed by HbA(1c) and diabetes duration) with brain volumes and vascular pathology on brain MRI and to assess whether the associations of diabetes with brain volumes are mediated by brain vascular pathology. RESEARCH DESIGN AND METHODS: Cross-sectional study of 1,713 participants in the Atherosclerosis Risk in Communities Neurocognitive Study (ARIC-NCS) (mean age 75 years, 60% female, 27% black, 30% prediabetes, and 35% diabetes) who underwent 3T brain MRI scans in 2011–2013. Participants were categorized by diabetes-HbA(1c) status as without diabetes (<5.7% [reference]), with prediabetes (5.7 to <6.5%), and with diabetes ([defined as prior diagnosis or HbA(1c) ≥6.5%] <7.0% vs. ≥7.0%), with further stratification by diabetes duration (<10 vs. ≥10 years). RESULTS: In adjusted analyses, compared with participants without diabetes and HbA(1c) <5.7%, participants with prediabetes and those with diabetes and HbA(1c) <7.0% did not have significantly different brain volumes or vascular pathology (all P > 0.05), but those with diabetes and HbA(1c) ≥7.0% had smaller total brain volume (β −0.20 SDs, 95% CI −0.31, −0.09), smaller regional brain volumes (including frontal, temporal, occipital, and parietal lobes; deep gray matter; Alzheimer disease signature region; and hippocampus [all P < 0.05]), and increased burden of white matter hyperintensities (WMH) (P = 0.016). Among participants with diabetes, those with HbA(1c) ≥7.0% had smaller total and regional brain volumes and an increased burden of WMH (all P < 0.05) compared with those with HbA(1c) <7.0%. Similarly, participants with longer duration of diabetes (≥10 years) had smaller brain volumes and higher burden of lacunes (all P < 0.05) than those with a diabetes duration <10 years. We found no evidence for mediation by WMH in associations of diabetes with smaller brain volumes by structural equation models (all P > 0.05). CONCLUSIONS: More-severe diabetes (defined by higher HbA(1c) and longer disease duration) but not prediabetes or less-severe diabetes was associated with smaller brain volumes and an increased burden of brain vascular pathology. No evidence was found that associations of diabetes with smaller brain volumes are mediated by brain vascular pathology, suggesting that other mechanisms may be responsible for these associations.